Identifikasi Jenis Serangga Pada Tanaman Jeruk BW (Citrus reticulata Blanco) Menggunakan Metode Yellow Plastik Trap Dan Pitfall Trap - Made Wiliam Binanta; Emantis Rosa; Gina Dania Pratami (CV. Multi Kreasi Media, 2025)
Various obstacles can occur in citrus cultivation, including insect attacks as pests, predators, decomposers, pollinators, and parasitoids. This research was carried out from November to December 2024 at the Lampung Agricultural Training Center, using two traps, yellow plastic traps and trap traps, which aimed to determine the type, composition, and structure of insects. The results of insect identification and composition with yellow plastic traps found 10 species, 5 orders and 13 insect families. The results of identification and composition of trap traps found 5 species, 4 orders and 5 insect families. Analysis results for insect structure: The relative abundance in both yellow plastic traps and trap traps had a value of one (even abundance); Diversity index at 2.560 was categorized as moderate; Dominance Index 0.094 (categorized as low). In trap traps, the diversity index was 1.598 (moderate); Dominance Index 0.243 (low).